Social Polarization and Economic Inequality: An Analysis of the Impact of Communist and Capitalist Policies on the Quality of Life of the Romani Community in Southern Muntenia - Miruna Pandele (Sociologie Românească)
This paper aims to provide an analysis of the social policies implemented in Romania in order to manage the Roma minority issue before and after the 1989 Revolution. Its main goal is to investigate whether Romania had a better social integration system put in place as to enable addressing the Roma minority issue during communism or afterwards. Today, the Romani community is dealing with systemic ethnic discrimination that brings about issues like poverty, unemployment, and homelessness. The lack of financial resources needed in order to survive in capitalism makes it hard for low-income families to ensure decent living conditions for themselves and their children. Negative attitudes towards the Romani affect their access to healthcare, counsel, education, and housing as they become systematically excluded from the social life of the majority and are made into outsiders in their own country. Thus, this study means to show the perspective of the Romani on the issue and how they feel the fall of communism has impacted their community by further exploring certain dimensions of social life in Romania - education, housing, and labour dynamics.